The effect of the supply chain exerting physical stress on the microbiological status of bottled natural mineral water - Tihanyi-Kovács, Renáta; Hanczné Lakatos, Erika; Ásványi, Balázs; Böröcz, Péter (Acta Agraria Debreceniensis, 2018)
Mineral water consumption increased dramatically in the last 30 years. One reason for this change lies in the changing consumer behaviour: consumers are increasingly recognizing the importance of healthy nutrition and appreciate the beneficial nutritional physiological properties of mineral water. Local mineral water harmonizes well with imported waters. Bottled mineral water may travel several hundred kilometres until it reaches consumers. In the present study, the dynamic mechanical vibration caused by transporting on public roads was simulated in laboratory vibration tests then samples were subjected to microbiological examinations in compliance with legislations currently in force. Due to this vibration, the initial microbe count increased by two orders of magnitude, while after terminating the 4-hour mechanical action it decreased gradually. Growing dynamics of microbes constituting the total germ count at 22 °C and 37 °C were almost similar.